A hybrid charging management strategy for solving the under-voltage problem caused by large-scale EV fast charging. (September 2021) - Ye, Rui; Huang, Xueliang; Chen, Zhong; Ji, Zhenya
Abstract: A hybrid charging management system (HCMS) is proposed to solve the nodal under-voltage problem in medium-voltage radial distribution networks caused by the concentrated high-power charging of electric vehicles (EVs), which contains a pre-centralized charging management platform (PCMP) and local charging management controllers (LCMCs) located at fast charging stations (FCSs). The proposed PCMP can formulate half-hourly charging power threshold plans for LCMCs based on a pre-centralized voltage regulation algorithm (PVRA) to prevent concerned nodes from under-voltage. Two sub-strategies, i.e., charging management sub-strategy (CMS) and cooperative control sub-strategy (CCS), are integrated in the LCMS, which can aggregate EVs charging at different FCSs to provide the voltage support service for the concerned node, so that the under-voltage problem of these concerned nodes can be alleviated. The load forecasting error, load uncertainty, and the need of the plug-and-play are considered as well. Finally, an IEEE 69-bus test system is used for simulation verification. Simulation results verify that the HCMS can be used to solve the nodal under-voltage problem caused by centralized high-power charging of EVs.